2022
DOI: 10.1149/10805.0071ecst
|View full text |Cite
|
Sign up to set email alerts
|

SiGe Epitaxial Growth on Si Substrate Using Al-Ge Paste

Abstract: We investigated the liquid-phase growth of silicon-germanium (SiGe) epitaxial layers formed on Si substrates by a simple and rapid process of screen-printing of Al-Ge paste followed by high temperature annealing. Aluminum (Al) and germanium (Ge) (7:3) mixed paste was prepared, screen-printed on a Si substrate and annealed in an infra-red (IR) furnace at peak temperatures between 800°C to 1000°C. After reaching the Al melting point at 660°C, the melted Al dissolves the Si surface and Ge powder in the paste form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…This method is a simple process using a conventional screen-printer and a furnace, and it has been confirmed that uniform SiGe layers with a thickness of more than 20 μm can be formed in a short processing time. [24][25][26][27][28] In this method, a liquid phase of Al-Ge-Si can be formed at a temperature below the mp of Si by screen-printing Al-Ge paste on a Si substrate. After the liquid phase is formed at high temperatures, cooling leads to the epitaxial growth of a SiGe layer at the interface of the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is a simple process using a conventional screen-printer and a furnace, and it has been confirmed that uniform SiGe layers with a thickness of more than 20 μm can be formed in a short processing time. [24][25][26][27][28] In this method, a liquid phase of Al-Ge-Si can be formed at a temperature below the mp of Si by screen-printing Al-Ge paste on a Si substrate. After the liquid phase is formed at high temperatures, cooling leads to the epitaxial growth of a SiGe layer at the interface of the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the formed SiGe layer have been found to strongly depend on fabrication parameters such as the Al/Ge ratio of the Al-Ge paste and the annealing temperature profile. 25,26,28) In this study, the effect of ambient gas during annealing on the growth of SiGe layers was investigated in order to determine the parameters of SiGe layer formation in liquid phase growth on Si substrates using Al-Ge paste.…”
Section: Introductionmentioning
confidence: 99%